Sweden, Russia, and the 1617 Peace of Stolbovo - Jönsson, Arne; Vetushko‑Kalevich, Arsenii (Brepols, 2023)
In 1617, after seven years of war between Sweden and Russia and talks facilitated by English and Dutch diplomats, the peace treaty of Stolbovo was signed. This important but little-studied document was to form the basis for relationships between Sweden and Russia for the next one hundred years, before it was replaced by the Peace of Nystad in 1721, and it had a huge influence on the lives of the people who lived in the region. This wide-ranging volume draws together contributions by scholars from Britain, Sweden, Germany, Estonia, Russia, and Finland to offer new insights into, and analysis of this peace treaty and its impact on the wider region during the seventeenth century. Covering disciplines including political and economic history, church history, and Slavonic and Classical philology, the chapters gathered here shed new light on, and provide a new understanding of, the Early Modern period in the Baltic Sea area.